Intra-oral Sebaceous Gland Tumours in Two Dogs. Issue 4 (November 2017) - Go, D.-M.; Lee, S.-H.; Woo, S.-H.; Kim, D.-Y.
Summary: A 12-year-old female miniature schnauzer and a 12-year-old neutered female cocker spaniel each had a grey–yellow nodular lesion arising from the gingiva. Microscopical examination showed that both nodules were composed of varied proportions of sebocytes and basal-type reserve cells with few ducts lined by stratified squamous epithelium. Based on the histopathological findings, the cases were diagnosed as sebaceous adenoma and sebaceous epithelioma, respectively. In man, the occurrence of sebaceous neoplasms in the oral cavity has been reported to some extent, but these lesions are very rare in animals. To the best of our knowledge, this is the first report of intra-oral sebaceous neoplasms in dogs. Intra-oral sebaceous epithelioma has never been reported in animals.